1993
DOI: 10.1002/nbm.1940060402
|View full text |Cite
|
Sign up to set email alerts
|

Pattern recognition of 31P magnetic resonance spectroscopy tumour spectra obtained in vivo

Abstract: Pattern recognition has been applied to the analysis of in vivo 31P NMR spectra. Using four different classes of tumour and three types of normal tissue, cluster analysis and artificial neural networks were successful in separating and classifying the majority of samples analysed. Although the phosphomonoester and P(i) regions appeared to be the most important spectral features, data representing the entire 31P spectrum were required for best separation of the tumour and tissue classes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…Using 31 P spectra of four types of tumours (Morris hepatoma, GH3 prolactinoma, RIF-1, MNU-induced mammary) and three types of normal tissue (brain, liver, skeletal muscle), cluster analysis and artificial neural networks correctly classified 62% of the tissues, while only 7% were assigned incorrectly with the rest being partly correct or not assignable. 123 Similar success rates were obtained from excised tissue specimen classified using 1 H spectra. 124,125 Recently, Preul et al 126 have classified and staged various brain tumours (glioblastoma grade II, III, IV, meningioma, metastases) in patients based on 1 H spectra.…”
Section: Oncologysupporting
confidence: 51%
“…Using 31 P spectra of four types of tumours (Morris hepatoma, GH3 prolactinoma, RIF-1, MNU-induced mammary) and three types of normal tissue (brain, liver, skeletal muscle), cluster analysis and artificial neural networks correctly classified 62% of the tissues, while only 7% were assigned incorrectly with the rest being partly correct or not assignable. 123 Similar success rates were obtained from excised tissue specimen classified using 1 H spectra. 124,125 Recently, Preul et al 126 have classified and staged various brain tumours (glioblastoma grade II, III, IV, meningioma, metastases) in patients based on 1 H spectra.…”
Section: Oncologysupporting
confidence: 51%
“…More recently they have been applied to the analysis of 'H MR spectra of tissue ex vivo (4) and in vivo (11) and 31P MR spectra of tumors in vivo (12).…”
Section: Introductionmentioning
confidence: 99%
“…By using cluster analysis, Howells et al reported a 62% of global success in the classification of in vivo 31 P-MRS spectra of tumors implanted in animals (53). In a more recent study, Nadal et al analyzed double extracts of 10 meningiomas and 10 glioblastomas in vitro by 1 H-MRS and 31 P-MRS, and grouped the data with multiple correspondences and ascending hierarchical classification methods.…”
Section: Classification Of Intracranial Tumors By Multivariate Discrimentioning
confidence: 98%